2020
DOI: 10.7717/peerj.8657
|View full text |Cite
|
Sign up to set email alerts
|

The role of age, sex, anthropometry, and body composition as determinants of physical fitness in nonobese children aged 6–12

Abstract: Purpose The determinants of physical fitness in children have been given limited attention. In particular, the relative role of chronological age, sex, anthropometry, and body composition in physical fitness of children has been barely investigated. This cross-sectional study investigated determinants of physical fitness using a set of predictive variables including, in addition to chronological age and sex, a large panel of anthropometric measurements as well as body composition. The study was carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
(67 reference statements)
4
20
0
1
Order By: Relevance
“…The results of the beforementioned study are contradictory with the statement made by Butterfield et al (2004), who found no association between longitudinal growth rates of height and body mass and improved running speed in children aged 11-13 years. The role of age in improving running speed in this period is possibly associated with an increasing stride length and frequency and neuromuscular coordination (Milanese et al, 2020). According to Whithall (2003) claims, the rate of progression of speed development is dramatically reduced in females at the age of 12, as we also confirm in our research.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the beforementioned study are contradictory with the statement made by Butterfield et al (2004), who found no association between longitudinal growth rates of height and body mass and improved running speed in children aged 11-13 years. The role of age in improving running speed in this period is possibly associated with an increasing stride length and frequency and neuromuscular coordination (Milanese et al, 2020). According to Whithall (2003) claims, the rate of progression of speed development is dramatically reduced in females at the age of 12, as we also confirm in our research.…”
Section: Discussionsupporting
confidence: 87%
“…Since that results in this research showed a moderate relation with explosive power and a weak relation with running speed and muscular strength and endurance, that is in relation findings of Malina et al (2004) and Milanese et al (2020)…”
Section: Growthsupporting
confidence: 58%
See 1 more Smart Citation
“…These studies reported an R 2 score of 54% [29] and 48% [30], respectively. Similarly, Milanese et al [26] showed a predictive equation for the 30-m dash test, but in children and considering only sex and age. Its R 2 value (R 2 = 0.55) was lower than that obtained in our study.…”
Section: Discussionmentioning
confidence: 97%
“…There is no doubt that age, sex [25][26][27]29,30], and BMI [25,28] are determining factors for fitness status. Nevertheless, this study [26] suggests that other variables, such as muscle fibre recruitment or muscular coordination, could be considered when developing prediction equations, because they may influence the performance on fitness tests. Moreover, Milanese et al [26] reported that FFM and FM% were not significant determinants of physical fitness.…”
Section: Discussionmentioning
confidence: 99%